Polycondensation History and New Results - Kricheldorf, Hans. (Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book reports on origin and history of polycondensation chemistry beginning in the first half of the 19th century. Furthermore, history and inventors of the most important polycondensates, such as Nylons, PET or polycarbonates, are described. The classical theory of step-growth polymerizations is discussed in the light of the latest experimental and theoretical results. Particular emphasis is laid on the role of cyclization reactions. Special categories of polycondensation processes are discussed in more detail: syntheses of hyperbranched and multicyclic polymers, non-stoichiometric polycondensations, interfacial polycondensations, solid state polycondensations, condensative chain polymerizations etc.